Steady State Levels of Tilmicocin and Enrofloxacin in Lung Tissues and Plasma of Broiler Chicks: A.A .Al –Khayyat , A .A. Shalash and L. A.Al-Ani - Al –Khayyat, A. A. (The Iraqi Journal of Veterinary Medicine, 2006)
A total of 54 broiler chicks were used to study the steady state levels ofTilmicocin and Enroflxacin in lung tissues and plasma.Microbiological assay, using Bacillus subtilis (ATCC 9225) or Saricinea leutus(ATCC 272) as test organisms for Enrofloxacin and Tilmicocin respectively,was employed to estimate the drugs levels.The birds were divided equally into two groups at the age of 21 days.The first group received Enrofloxacin at an estimated dose of 10 mg/kg bodyweight in drinking water for three consecutive days, while Tilmicocin was givenin the same way but at a dose of 15 mg/kg body weight .Samples of lung tissuesand plasma were collected from birds of each group at scheduled periods (6, 12,18, 24, 36, 48, 72, 96 and 120 hours after beginning of treatment).The plateau of enrofloxacin level in lung tissues and plasma wasachieved after approximetly 12 hours of the beginning of treatment and rangedfrom 0.90 – 1.26 ug/ gram and 0.50 – 0.86 ug/ ml respectively.The level declines immediately after termination of treatment (72 hours).Tilmicocin plateau level was achieved after 18 hours and ranged in lung tissuesand plasma from 2.25 -2.70 ug /gram and 0.98 -1.65 ug/ml respectively but theplatuae level continue through out the whole time of the experiment (120 hours).The ratio of Tilmicocin level in the lung tissues to plasma wassignificantly higher than that of enrofloxacin at 12 and 48 hours periods.It was concluded that Tilmicocin may be more effective thanEnrofloxacin in respiratory diseases.